Consideraciones a tener en cuenta en la exportación de fertilizantes a base de roca fosfórica a Costa Rica caso: Empresa Fosfatos del Huila S.A (2023)
This research focuses on analyzing the considerations that should be taken into account when exporting fertilizers based on phosphate rock to international markets, with the purpose of allowing the company fosfatos del Huila S.A. to access the Costa Rican market with its products Ground Phosphate 251020 and Unground Phosphate 251010, in order to achieve its business vision of expanding in the Central American region. The methodology used is based on an exhaustive review of the available information on companies that have carried out exports in the department of Huila, focusing especially on the sector of fertilizers made from phosphate rock. In this descriptive study, the information was compiled through reports provided by both the Antonio Nariño University and the company Fosfatos del Huila S.A., as well as preliminary research. The findings of this study will offer concrete recommendations to the company, which will be useful for the company to determine if it is viable to enter the Costa Rican market, which will allow a broader understanding of the Central American region and the countries that compose it; Therefore, in this research three main specific objectives were structured that will help to understand the phenomena of the international market, which are to evaluate the production capacity of the exportable supply and the agroindustrial sector, the realization of a study of international supply and demand. Finally, to review the main logistic aspects of international physical distribution, customs and marketing channels of fertilizers based on phosphate rock, thus developing a study with a focus on international trade and contribute to the regional economy and exports.